Neurological Manifestations of Celiac Disease: - Ashkani-Esfahani, Soheil; Bagheri, Fereshte; Pishva, Ehsan; Malekzadeh, Reza; Karimi, Ali Asghar; Borhani Haghighi, Afshin (Galen Medical Journal, 2013)
Celiac disease (CD) is a rare malabsorption syndrome mainly occurring in childhood which is now recognized as the most common food intolerance disease in the world. CD is associated with a wide spectrum of extra intestinal manifestations. Neurological involvements of CD were first attributed to malabsorption due to changes in the mucosal architecture of the small intestine. Neurological manifestations were more frequent in middle-aged adults, but were rare in children. The most common central nervous system manifestations include cerebellar malfunctions, seizures, dementia, multiple sclerosis like presentations, motor neuron diseases, headaches, movement disorders, and neuro-psychiatric presentations. On the other hand, the peripheral nervous system involvement includes different types of peripheral neuropathies and muscular involvements. In this study, we embarked on a short review to go through the neurological presentations and problems of CD.